2018
DOI: 10.1016/j.redox.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K: Redox-modulation, prevention of mitochondrial dysfunction and anticancer effect

Abstract: This review is directed to the redox-modulating properties and anticancer effect of vitamin K. The concept is focused on two aspects: (i) redox-cycle of vitamin K and its effect on the calcium homeostasis, “oncogenic” and “onco-suppressive” reactive oxygen species and the specific induction of oxidative stress in cancer; (ii) vitamin K plus C as a powerful redox-system, which forms a bypass between mitochondrial complexes II and III and thus prevents mitochondrial dysfunction, restores oxidative phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 89 publications
1
71
0
3
Order By: Relevance
“…In nature, plant forms (vitamin K1 and phylloquinone) and bacterial forms (vitamin K2 and menaquinones) are the isoprenologs of vitamin K. After being ingested from the intestine, vitamin K is transported to the liver with triacylglycerol-rich lipoprotein, where vitamin K1 is transformed into vitamin K2 [41]. The transformed vitamin K2 is transported to extrahepatic tissues, such as bones, arteries, and macrophages, by low-density lipoproteins [42]. In extrahepatic tissue, menaquinone-4 is the major form of vitamin K with a mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, plant forms (vitamin K1 and phylloquinone) and bacterial forms (vitamin K2 and menaquinones) are the isoprenologs of vitamin K. After being ingested from the intestine, vitamin K is transported to the liver with triacylglycerol-rich lipoprotein, where vitamin K1 is transformed into vitamin K2 [41]. The transformed vitamin K2 is transported to extrahepatic tissues, such as bones, arteries, and macrophages, by low-density lipoproteins [42]. In extrahepatic tissue, menaquinone-4 is the major form of vitamin K with a mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that mitochondria function normally even in glycolysis-dependent cancer cells, and that glutamine metabolism and FAO are activated [ 50 , 51 , 52 , 54 , 55 ]. In vitro and in vivo experiments have shown that inhibitors of mitochondrial OXPHOS, such as metformin, phenformin, and menadione, suppress CSC traits [ 132 , 163 , 164 , 165 , 166 , 167 ]. Also, since mitochondria are derived from a prokaryote that originally parasitized eukaryotic cells, it is known that its function can be inhibited by treatment with various antibiotics [ 17 , 18 , 19 , 20 , 168 , 169 , 170 ].…”
Section: Therapeutic Strategies For Targeting Csc Metabolismmentioning
confidence: 99%
“…Antioxidants compound targeted to reduce ROS and increase antioxidant enzymes that result in protection against ischemic injury. Moreover, there is evidence that overexpression of antioxidant enzymes can reduce oxidative stress in oxygen-glucose-deprived neurons and global cerebral ischemia [101,102]. Although Vitamin K is not known as a classical antioxidant, research reports that Vitamin K1 and K2 (menaquinone-4) potently inhibit glutathione depletion-mediated oxidative cell death.…”
Section: Plos Onementioning
confidence: 99%